Autophagy Dysfunction and Oxidative Stress, Two Related Mechanisms Implicated in Retinitis Pigmentosa - Moreno, Mari-Luz; Mérida, Salvador; Bosch-Morell, Francisco; Miranda, María; Villar, Vincent M. (Frontiers in Physiology, 2018)
Retinitis pigmentosa (RP) is one of the most common clinical subtypes of retinal degeneration (RD), and it is a neurodegenerative disease that could cause complete blindness in humans because it ultimately affects the photoreceptors viability. RP afflicts an estimated 1.5 million patients worldwide. The retina is highly susceptible to oxidative stress which can impair mitochondrial function. Many retina pathologies, such as diabetic retinopathy and secondary cone photoreceptor death in RP, have been related directly or indirectly with mitochondrial dysfunction. The possible role of autophagy in retina and cell differentiation is described and also the implications of autophagy dysregulation in RP. The present review shows the crucial role of autophagy in maintaining the retina homeostasis and possible therapeutic approaches for the treatment of RP.